The Topic of the Mater Dolorosa in Dominican Meditations: scenes of Mary Bidding Farewell to Jesus at Bethany - Kiszkowiak, Katarzyna (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The topic of the Mater Dolorosa in Dominican Meditations, an extensive old-Polish apocryphal workdealing with The Passion, written around the year 1532 at the Dominican Monastery of the Holy Trinityin Kraków, is discussed. The article examines the amplifications by the anonymous author of that workin relation to the extremely brief reference in the Gospels to the Holy Mother’s participation in Jesus’Passion: the only part of the New Testament to make any mention of the Holy Virgin Mary’s presenceat Christ’s death is the Gospel according to St. John 19: 25–27. A further objective of the article was toidentify the main rhetorical strategies applied in the adaptations of the Biblical text: the apotheosis ofMary’s motherhood and the glorification of the spiritual links joining Mary and Jesus.